Filipino values through music activities a module of music activities teaching Philippine values - Mabilog, Joseph D.
The researcher proposes to address this problem through the integration of music activities in teaching Philippine values in the Christian living, the counterpart of the values subject in Seven Pillars Catholic School. These music activities will make students experience the basic elements of music and learn them as well.The project aims to create a module as a resource for teachers these music activities that are coupled by original children's songs recorded in CDs.